Β‐Aminoacrylate Synthetic Hydrogels: Easily Accessible and Operationally Simple Biomaterials Networks. Issue 49 (8th November 2018) - Fenton, Owen S.; Andresen, Jason L.; Paolini, Marion; Langer, Robert
Abstract: The development of new material platforms can improve our ability to study biological processes. Here, we developed a water‐compatible variant of a click‐like polymerization between alkynoates and secondary amines to form β‐aminoacrylate synthetic polyethylene glycol (PEG) based hydrogels. These materials are easy to access—PEG alkynoate was synthesized on a 100 gram scale and the amines were available commercially; these materials are also operationally simple to formulate—gel formation occurred upon simple mixing of precursor solutions without the need for initiators, catalysts, nor specialized equipment. Three‐dimensional cell culture experiments also indicated cytocompatibility of these gels with >90 % viability retained in THP‐1 and NIH/3T3 cells after 72 hours in culture. This hydrogel system therefore represents an alternative platform to other click and click‐like hydrogels with improved accessibility and user‐friendliness for biomaterials application. Abstract : A water‐compatible variant of a click‐like polymerization between alkynoates and secondary amines to form β‐aminoacrylate synthetic polyethylene glycol (PEG) based hydrogels was developed. Cell culture experiments indicate cytocompatibility of these gels with >90 % viability retained in THP‐1 and NIH/3T3 cells after 72 hours in culture.